Solare Aktivitätsschwankungen und Niederschlagsfluktuationen in Westafrika - Klaus, Dieter (ERDKUNDE, 1977)
The annual totals of precipitation recorded at West African observation stations during the period 1921-73 were allied with the phases of maximal and minimal solar activity. The phase of minimal numbers of sunspots present macro-regionally significant deviations of the precipitation totals from the long-term mean. Negative deviations of precipitation in the Senegalese Mauritanien coastal zone, together with positive deviations of annual precipitation totals from the long-term mean, can be meaningfully established two years before the occurrence of the sunspot minimum. Two years after a sunspot maximum there are considerable precipitation deficits almost everywhere in the West African region. The homogeneous time series of the annual precipitation totals of 18 West African stations were subjected to variance spectrum analysis. The spatial ordering of variance shares, as explained over an eleven and twenty-two year period, shows that the time series of the West African precipitation totals are by no means uniformly determined by this periodicity. On the contrary, areas can be defined in which the single or, as the case may be, the double sunspot cycle is indentifiable as being highly significant in the precipitation fluctuations. The annual movements of the ITC are theoretically noted down by means of their spatial precipitation distributions, and investigated in respect of their periodicity. In the west of West Africa a 13 year period clearly emerges. A 24 and 30 year period can be established on the basis of the discharge data for the Senegal and Niger rivers, which is also repeated in the frequency of occurrence of the mixed and meridional forms of circulation over Europe.